Analisis Nilai Tambah Sale Pisang pada Industri Rumahtangga â€œKejar Usaha Lestariâ€ di Desa Pallimae Kecamatan Poleang Kabupaten Bombana - Inna, Mutma; Geo, La Ode; Gafaruddin, Abdul (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This research aims; (1) to describe process diversity in the processing of banana into banana sale; (2) to know how much the added value resulting from the processing of bananas. The location of this research is at home industry â€œKejar Usaha Lestariâ€ at Pallimae Village, Poleang District, Bombana Regency.This location was chosen by purposive, sampling in whiel the owner of the business became respondent of the research. The primary data was collected through direct interview using a questionnaire. The data is processed using Hayami, et all 1987. The results showed that(1) processing of banana into banana sale in â€œKejar Usaha Lestariâ€ has developed because it has provided four kind of tastes banana sale, that is fresh banana sale, white sugar flavored banana sale, brown sugarÂ  flavored banana , and peanuts flavored; (2) the added value produced in â€œKejar Usaha Lestariâ€ approximately, that is fresh banana sale Rp 11.878,67Â  a kilogram, peanuts flavored banana sale Rp 11.284,16 a kilogram, white sugar flavored banana sale Rp 10.054,16, brown sugarÂ  flavored banana Rp 11.817,49.